KONDISI KEUANGAN DAN KEBERLANGSUNGAN USAHA PERUSAHAAN FARMASI SAAT COVID-19 - Farahia , Emmadithea; Nugroho, Vidyarto (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study was to analyze whether Covid-19 had its impact on the financial performance and business continuity or going concern of pharmaceutical companies listed on the Indonesia Stock Exchange from period 2019 to 2021 as samples. The data used in this study came from observations and documentation studies of the financial and annual reports of 10 pharmaceutical companies that have been audited and published as the requirements. This study used three techniques to analyze the datas, which were descriptive statistics, Paired Sample T-Test, and Altman Z-Score Bankruptcy Prediction Model with IBM SPSS Statistics 26. The results of this study was Covid-19 pandemic had no significant impact on the financial performance (using liquidity and profitability ratio for measurement) and business continuity or going concern of the 10 pharmaceutical companies listed on the Indonesia Stock Exchange when calculated before and after the announcement (2019-2021).